Development of a radiographic index to assess the tarsal involvement in patients with spondyloarthropathies. Issue 4 (1st April 2002) - Pacheco-Tena, C; Londoño, J D; Cazarín-Barrientos, J; Martínez, A; Vázquez-Mellado, J; Moctezuma, J F; González, M A; Pineda, C; Cardiel, M H; Burgos-Vargas, R
Abstract : Objective: To develop and test an index to evaluate the radiographic changes that occur in the tarsus and adjacent areas of the foot in patients with spondyloarthropathies (SpA). Methods: The spondyloarthropathy tarsal radiographic index (SpA-TRI) was developed in three consecutive steps: ( a ) detection of descriptors after reviewing 70 radiographic files; ( b ) descriptor gradation and subsequent modifications performed by a consensus committee, and ( c ) interobserver variability assessed by three blinded and independent observers on 272 radiographs: anteroposterior 118, lateral 90, oblique 64 from 121 patients with SpA, and intraobserver variability on 75 radiographs from 25 patients with SpA. Statistical analysis included percentage of agreement and κ test. SpA-TRI score ranges from 0 to 4 (0=normal; 1=osteopenia or suspicious findings; 2=definite joint space narrowing, bony erosion(s), periosteal whiskering, or enthesophyte(s) in the plantar fascia or Achilleal tendon attachments; 3=para-articular enthesophyte(s); 4=bony ankylosis (joint space fusion or complete bridging)). Results: Complete agreement for every evaluation was >40%, and discordance >1 grade was <15%. The κ scores among the three observers were acceptable for all the single projections: oblique (0.52, 0.36, 0.35), lateral (0.50, 0.42, 0.56), and anteroposterior (0.40, 0.41, 0.21) views. The combination of lateral and oblique views achieved the highest concordance rates (0.72, 0.33, 0.66), surpassing that of the three projections altogether (0.34, 0.58, 0.37). In every case the concordance was comparable with that of sacroiliac joints (0.47, 0.41, 0.34); intraobserver concordance showed a similar trend. Conclusion: The SpA-TRI is an index that includes the most prominent features of tarsal disease and adjacent areas of the foot in SpA and grades them accordingly, it has an adequate reproducibility, and is suitable for use with two or more projections, preferably the combination of oblique and lateral.